Catastrophic Neurological Complications in 2 Patients With Sickle Cell Disease and COVID-19 - Karen Clarke MD, MSc, MPH; Karima Benameur MD; Zanthia Wiley MD; Yoo Mee Shin MD; Mohamad Moussa MD; Fuad El Rassi MD; Morgan McLemore MD (SAGE Publishing, 2022)
Severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection is commonly associated with neurological complications. Patients with sickle cell disease are at increased risk of developing neurologic complications throughout their lifetimes and often have underlying cardiopulmonary comorbidities that may predispose them to poor outcomes during serious infections. In this case series, we describe 2 patients with sickle cell disease who developed devastating neurologic complications following SARS-CoV-2 infection, which ultimately led to brain edema and death. We highlight the unusual manifestations of coronavirus disease 2019 in patients with sickle cell disease and address the risk of these patients to develop catastrophic neurologic injury due to COVID-19, if not recognized promptly.